2015
DOI: 10.4049/jimmunol.1402678
|View full text |Cite
|
Sign up to set email alerts
|

Core Fucosylation of IgG B Cell Receptor Is Required for Antigen Recognition and Antibody Production

Abstract: Ag recognition and Ab production in B cells are major components of the humoral immune response. In the current study, we found that the core fucosylation catalyzed by α1,6-fucosyltransferase (Fut8) was required for the Ag recognition of BCR and the subsequent signal transduction. Moreover, compared with the 3-83 B cells, the coalescing of lipid rafts and Ag-BCR endocytosis were substantially reduced in Fut8-knockdown (3-83-KD) cells with p31 stimulation and then completely restored by reintroduction of the Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 43 publications
(56 reference statements)
1
78
0
Order By: Relevance
“…4 Another most recent example is that in humoral immune response, core-fucosylation of IgG B cell receptor was shown to mediate antigen recognition and cell signal transduction. 5 Alteration of core-fucosylation is frequently found to be closely related to human diseases including liver cancer, pancreatic cancer, lung cancer, breast cancer, etc. 6 A well-known example is α-fetoprotein, which was found highly core-fucosylated specifically in hepatocellular carcinoma, but not other liver diseases.…”
mentioning
confidence: 99%
“…4 Another most recent example is that in humoral immune response, core-fucosylation of IgG B cell receptor was shown to mediate antigen recognition and cell signal transduction. 5 Alteration of core-fucosylation is frequently found to be closely related to human diseases including liver cancer, pancreatic cancer, lung cancer, breast cancer, etc. 6 A well-known example is α-fetoprotein, which was found highly core-fucosylated specifically in hepatocellular carcinoma, but not other liver diseases.…”
mentioning
confidence: 99%
“…The loss of the core Fuc on N-glycans of the TGF-β1 receptor correlates with markedly reduced TGF-β signaling via SMAD2, and both cell and lung defects were at least partially rescued by TGF-β. Most recently it has been shown that mice lacking FUT8 exhibit reduced IgG production in response to antigenic stimulation due to a requirement for core Fuc on N-glycans of the IgG-B cell receptor [83]. …”
Section: Pathway-specific Glycans That Affect Postnatal Developmentmentioning
confidence: 99%
“…Since Fut8 is the sole glycosyltransferase for core fucosylation, the Fut8 −/ − mice, which were generated in our laboratory, were applied here to establish a Fut8 ‐deleted mouse ovarian epithelial cell model . Immunohistochemistry assays with LCA show that core fucosylation was abolished in Fut8 −/− mouse ovary (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Ovary epithelial cells were obtained from homozygous wild type (FUT8 +/+ ), heterozygous (FUT8 +/− ) and Fut‐8 gene‐knockout (FUT8 −/− ) mice . In detail, ovarian tissues were removed from the mice following by incubation in hyaluronidase (100 U) and collagenases (300 U) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation